The role of the digital story in developing creative thinking among primary school students at Iksal C School - Drawshy, Majeda Mazen (Journal of Curriculum and Teaching Methodology, 2025)
The study aimed to reveal the role of the digital story in the development of creative thinking among primary school students in one of the schools of the Palestinian Interior, and to achieve the goal of the study, the researcher relied on the semi-experimental curriculum, and the study sample consisted of (48) male and female students at Excel C school, in the subject of the Arabic language, the researcher divided the sample into two groups, where the control group consisted of (24) male and female students who were taught in the traditional way, and (24) male and female students of the experimental group who were taught using the digital story, the researcher verified the truthfulness of the creative thinking test (Torrance) for the year 1973, by applying it to a survey sample consisting of (20) students from a community The study is out of her sample. The results showed statistically significant differences at the level of significance (0.05=α) between the two computational averages of the telemetry of creative thinking (as a whole) attributable to the group (experimental, control) in favor of the experimental group taught using the digital story method. The study recommended designing digital stories in the Arabic language and enriching the Arabic content of this type of stories.